Sprout Caffeoylquinic Acid Profiles as Affected by Variety, Cooking, and Storage - Khaksar, Gholamreza; Cheevarungnapakul, Ketthida; Boonjing, Patwira; Sirikantaramas, Supaart (Frontiers in Nutrition, 2021)
Various health-promoting properties inherent to plant-based foods have been attributed to their rich bioactive compounds, including caffeoylquinic acids (CQAs). The potential health benefits of CQAs have been well documented. While sprouts are widely recognized as health-promoting foods owing to their high phytonutrient content, our knowledge regarding the effect of cooking and storage, commonly practiced by consumers, on the CQA content remains limited. First, sunflower sprouts were found to have the highest total CQA content (~ 22 mg/g dry weight) out of eleven commonly available sprouts. Then, the effect of variety, cooking, and low-temperature storage on the CQA profile of sunflower sprouts was investigated. Among the four different varieties of sunflower sprouts, variety 1 harbored the highest total CQA content. Notably, cooking adversely affected the CQA content of sunflower sprouts relative to the uncooked samples in a time-dependent manner, possibly due to the heat sensitivity of CQAs. Under simulated home-refrigeration storage conditions, we observed a significant decline in the content of major CQA compounds (5-monoCQA and 3,5-diCQA) at days 10 and 13 of storage. The results obtained herein provide consumers and food industrialists with increased insight into the effect of cooking and refrigeration on the nutritional value of sunflower sprouts.